Вивчення ролі NO та актинових філаментів у відповіді рослин на дію холоду - Плоховська, С.Г.; Красиленко, Ю.А.; Ємець, А.І.; Блюм, Я.Б. (Фактори експериментальної еволюції організмів, 2015)
Aims. It has been shown in a number of studies that low temperature leads to significant changes in the organization of cytoskeleton structures. Recent studies have shed light on the importance of NO, a ubiquitous signaling molecule in eukaryotes, for plant tolerance to freezing. Methods. In this work we studied the effect of cold and SNP (NO donor) on organization of actin filaments in the cells of the root seedlings A. thaliana (GFP-ABD2-GFP) using confocal laser scanning microscope. Results. Observed disorientation and partially depolymerization of actin filaments in the most cells of the transition zone and individual cells were found. Effect of SNP stimulates restoration of actin filaments; there were found an extensive network of renewal filaments structures after SNP treatment. Conclusions. Our data have shown for the first time a negative effect of low temperature on organization and orientation of the actin filaments in various cell types of the main roots of A. thaliana. We have found that disorientation microfilaments reversed by exogenous donor of NO, which correlates positively with respect to cold. Keywords: cytoskeleton, actin filanents, sodium nitroprusside (SNP), green fluorescent protein (GFP), actin binding domen 2 (ABD2).